The Influence of Problem-Based Learning Model on Student Learning Outcomes in the Theme of Technology Development Class III SD Negeri 101731 Kp. Lalang - Rahmi, Latifa; Landong, Ahmad (Widyagogik, 2023)
This research aims to determine the learning outcomes on the theme of technological development for class III students who are taught using the Problem Based Learning learning model and to examine the effect of the Problem Based Learning Learning Model on student learning outcomes on the theme of technological development for class III students. The population of this study were all students of class III SD, totaling 58 people consisting of 2 classes III A and III B. This study used experimental research. The test results using the independent sample t-test formula, obtained tcount = 2.43 and ttable = 2.04. Thus tcount ttable = 2.43 2.04, the average value of the experimental class and control class, where the experimental class is 68.33 and the control class is 59.56. It can be concluded that there is an influence of the problem-based learning (PBL) learning model on student learning outcomes in thematic subjects on the theme of technological development for class III students at SD Negeri 101731 Kp. Lalang.